Fibroblast Growth Factor 22 Inhibits ER Stress-Induced Apoptosis and Improves Recovery of Spinal Cord Injury - Zhu, Sipin; Chen, Mengji; Chen, Min; Ye, Jiahui; Ying, Yibo; Wu, Qiuji; Dou, Haicheng; Bai, Liyunian; Mao, Fangmin; Ni, Wenfei; Yu, Kehe (Frontiers in Pharmacology, 2020)
Currently, inhibiting or reducing neuronal cell death is the main strategy to improve recovery of spinal cord injury (SCI). Therapies using nerve growth factors to treat SCI mainly focused on reducing the area damaged by postinjury degeneration to promote functional recovery. In this report, we investigated the mechanism of ER (endoplasmic reticulum) stress-induced apoptosis and the protective action of fibroblast growth factor 22 (FGF22) in vivo. Our results demonstrated that ER stress-induced apoptosis plays a significant role in injury of SCI model rats. FGF22 administration promoted recovery and increased neuron survival in the spinal cord lesions of model mice. The protective effect of FGF22 is related to decreased expression of CHOP (C/EBP-homologous protein), GRP78 (glucose-regulated protein 78), caspase-12, X-box binding protein 1 (XBP1), eukaryotic initiation factor 2α (Eif-2α) and Bad which are ER stress-induced apoptosis response proteins. Moreover, FGF22 administration also increased the number of neurons and the expression of growth-associated protein 43 (GAP43) which was related to axon regeneration. We also demonstrated that the protective effect of FGF22 effectively reduces neuronal apoptosis and promotes axonal regeneration. Our study first illustrated that the function of FGF22 is related to the inhibition of ER stress-induced cell death in SCI recovery via activation of downstream signals. This study also suggested a new tendency of FGF22 therapy development in central neural system injuries, which involved chronic ER stress-induced apoptosis.